Loss of Cytosolic Phosphoglucomutase Compromises Gametophyte Development in Arabidopsis(1)([W])([OA]) - Egli, Barbara (American Society of Plant Biologists, 2010)
Cytosolic phosphoglucomutase (cPGM) interconverts glucose-6-phosphate and glucose-1-phosphate and is a key enzyme of central metabolism. In this study, we show that Arabidopsis (Arabidopsis thaliana) has two cPGM genes (PGM2 and PGM3) encoding proteins with high sequence similarity and redundant functions. Whereas pgm2 and pgm3 single mutants were undistinguishable from the wild type, loss of both PGM2 and PGM3 severely impaired male and female gametophyte function. Double mutant pollen completed development but failed to germinate. Double mutant ovules also developed normally, but approximately half remained unfertilized 2 d after pollination. We attribute these phenotypes to an inability to effectively distribute carbohydrate from imported or stored substrates (e.g. sucrose) into the major biosynthetic (e.g. cell wall biosynthesis) and respiratory pathways (e.g. glycolysis and the oxidative pentose phosphate pathway). Disturbing these pathways is expected to have dramatic consequences for germinating pollen grains, which have high metabolic and biosynthetic activities. We propose that residual cPGM mRNA or protein derived from the diploid mother plant is sufficient to enable double mutant female gametophytes to attain maturity and for some to be fertilized. Mature plants possessing a single cPGM allele had a major reduction in cPGM activity. However, photosynthetic metabolism and growth were normal, suggesting that under standard laboratory conditions cPGM activity provided from one wild-type allele is sufficient to mediate the photosynthetic and respiratory fluxes in leaves.